Synthesis and Biological Evaluation of Quinolinone Compounds as SARS CoV 3CL(pro) Inhibitors - Sun, Yuanpei (Chin J Chem, 2013)
SARS CoV 3CL(pro) is known to be a promising target for development of therapeutic agents against the severe acute respiratory syndrome (SARS). A quinolinone compound 1 was selected via virtual screening, and it was synthetized and tested for enzymatic inhibition in vitro. Compound 1 showed potent inhibitory activity (IC(50)=0.44 µmol/L) toward SARS CoV 3CL(pro). Further work on a series of quinolinone derivatives resulted in the discovery of the most potent compound 23, inhibiting SARS CoV 3CL(pro) with an IC(50) of 36.86 nmol/L. The structure‐activity relationships were also discussed.